2004
DOI: 10.3748/wjg.v10.i6.852
|View full text |Cite
|
Sign up to set email alerts
|

Establishment ofHelicobacter pyloriinfection model in Mongolian gerbils

Abstract: AIM:To establish a stable and reliable model of Helicobacter pylori infection model in Mongolian gerbils and to observe pathological changes in gastric mucosa in infected animals. METHODS:Mongolian gerbils were randomly divided into 18 groups; 6 groups were infected with H pylori clinical strain Y06 (n=6, groups Y), 6 groups were infected with H pylori strain NCTC11637 (n=6, groups N), and 6 uninfected groups as negative controls (n=4, groups C). H pylori suspensions at the concentrations of 2×10 8 and 2×10 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The use of various animal species and bacterial strains results in a large variability in the reported results ( 40 ). Mongolian gerbils are a unique model due to their low incidence of naturally occurring gastritis and bacterial disease, and have, therefore, commonly been used for studying infection with a standard strain of H. pylori (ATCC43504) ( 41 ). The results of the current study demonstrate that, concordant with previous results from patients ( 28 ), 6–12 months of infection in these gerbils did not significantly alter PTEN expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…The use of various animal species and bacterial strains results in a large variability in the reported results ( 40 ). Mongolian gerbils are a unique model due to their low incidence of naturally occurring gastritis and bacterial disease, and have, therefore, commonly been used for studying infection with a standard strain of H. pylori (ATCC43504) ( 41 ). The results of the current study demonstrate that, concordant with previous results from patients ( 28 ), 6–12 months of infection in these gerbils did not significantly alter PTEN expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection in the gastric mucosa of Mongolian gerbils exhibits a significant level of gastric inflammation after multiple inoculations with a high concentration of bacterial challenge, contributing to increased infection rates [ 73 ]. In one study, Mongolian gerbils developed moderate atrophy after 12 months of infection with H. pylori 26695, whereas no metaplasia was observed until 12 months, and light metaplasia was observed after 18 months [ 74 ].…”
Section: Animal Models In Evaluating H Pylori -Med...mentioning
confidence: 99%
“…It is well established that H. pylori infection is a major risk factor for intestinal GC, with the International Agency for Research on Cancer classifying it as a class I carcinogen as early as 1994 ( 30 ). Animal infection models have shown that H. pylori can induce GC in Mongolian gerbils, closely resembling the Correa model of intestinal GC ( 31 , 32 ). Infection with H. pylori leads to chronic inflammation of the gastric mucosa, destruction of oxytocin cells, an increase in stomach pH, and an imbalance in the gastric microbiota, resulting in decreased H. pylori levels and colonization by non- H. pylori bacteria.…”
Section: Intestinal Flora and Stomach Cancermentioning
confidence: 88%